The direct impact of climate change on regional labour productivity - Tord Kjellstrom; R. Sari Kovats; Simon J. Lloyd; Tom Holt; Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2008)
Global climate change will increase outdoor and indoor heat loads, and may impair health and productivity for millions of working people. This study applies physiological evidence about effects of heat, climate guidelines for safe work environments, climate modelling and global distributions of working populations, to estimate the impact of two climate scenarios on future labour productivity. In most regions, climate change will decrease labour productivity, under the simple assumption of no specific adaptation. By the 2080s, the greatest absolute losses of population based labour work ability as compared with a situation of no heat impact (11-27%) are seen under the A2 scenario in South-East Asia, Andean and Central America, and the Caribbean. Climate change will significantly impact on labour productivity unless farmers, self-employed and employers invest in adaptive measures. Workers may need to work longer hours to achieve the same output and there will be economic costs of occupational health interventions against heat exposures.
Keywords: 330; climate change; heat; work; labour productivity; Klimaveränderung; Treibhausgas; Arbeitsproduktivität; Gesundheitsrisiko; Regionale Entwicklung; Prognose; Welt